2022
DOI: 10.1111/aji.13582
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum vitamin D level during pregnancy and recurrent spontaneous abortion: A systematic review and meta‐analysis

Abstract: Problem Previous studies had shown that there might be an association between serum vitamin D concentrations and the occurrence of recurrent spontaneous abortion (RSA). However, the conclusions remained controversial. The objective of this study was to systematically review the evidence for an epidemiological association between vitamin D and RSA. Method of study The literature search was performed in the following databases: PubMed, Web of Science, Embase and Chinese databases. The I2 statistic was used to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…For instance, Tamblyn et al (2022) conducted a systematic review and meta-analysis and found that vitamin D deficiency and insufficiency were associated with miscarriage. Similarly, Chen et al (2022) found that patients with recurrent miscarriage had significantly lower serum 25OHD concentrations than normal pregnant women, and vitamin D deficiency during pregnancy might be a high risk factor for recurrent miscarriage. However, some studies did not find this association ( Subramanian et al , 2022 ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…For instance, Tamblyn et al (2022) conducted a systematic review and meta-analysis and found that vitamin D deficiency and insufficiency were associated with miscarriage. Similarly, Chen et al (2022) found that patients with recurrent miscarriage had significantly lower serum 25OHD concentrations than normal pregnant women, and vitamin D deficiency during pregnancy might be a high risk factor for recurrent miscarriage. However, some studies did not find this association ( Subramanian et al , 2022 ).…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have shown that women with recurrent miscarriage have a reduction in 25OHD levels and decreased expression of 1-α-hydroxylase and vitamin D receptors at the maternal–fetal interface ( Wang et al , 2016 ; Yan et al , 2016 ; Li et al , 2017 ). Multiple recent meta-analyses have also shown that pregnant women with vitamin D insufficiency/deficiency have a significantly higher risk of miscarriage and recurrent miscarriage ( Chen et al , 2022 ; Tamblyn et al , 2022 ). However, there is a lack of high-quality evidence from randomized controlled studies.…”
Section: Introductionmentioning
confidence: 99%
“…Following deduplication, 673 meta-analyses remained, which underwent title and abstract screening with 123 meta-analyses selected for full-text screening. Finally, 16 meta-analyses met the inclusion criteria for this umbrella review [15][16][17][18][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Search Resultsmentioning
confidence: 99%
“… 64 In a meta-analysis of 14 studies, women experiencing recurrent miscarriages had significantly lower serum vitamin D concentrations compared with those who completed a normal pregnancy. 65 Despite these findings, it remains unclear whether vitamin D supplementation improves fertility or decreases the risk of adverse pregnancy outcomes such as pre-eclampsia, low birth weight and neonatal mortality. 60 …”
Section: Review Of Conditions Associated With Vitamin D Deficiencymentioning
confidence: 99%